2008
DOI: 10.1111/j.1438-8677.2008.00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservation genetics of the endangered Iberian steppe plant Ferula loscosii (Apiaceae)

Abstract: Ferula loscosii (Lange) Willk (Apiaceae) is a threatened endemic species native to the Iberian Peninsula. The plant has a narrow and disjunct distribution in three regions, NE, C and SE Spain. Genetic variability within and among 11 populations from its natural distribution was assessed using allozymes. Intermediate levels of genetic diversity were detected in F. loscosii (P(99%) = 36.83; H(E) = 0.125; H(T) = 0.152). However, the highest genetic diversity (58%) corresponded to the threatened populations from S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…Furthermore, most of the NE Spain AFLP fragments represent a subset of the total allelic variation found across the species, and all the analysed AFLP population diversity estimates ( hs , Hs , P 95 P 99 ) showed significant higher values in the southern Iberian populations of F. loscosii than in the northeastern Iberian ones (Table 1). These results concur with an allozyme study that also shows a higher allelic variability in the southern Iberian populations and an allelic sub‐representation in the NE Spain range (Pérez‐Collazos & Catalán 2008). The two independent molecular sources point towards to an earlier origin of the southern Iberian populations and a later derived origin of the northeastern ones; they also reject the AC hypothesis for this steppe plant in the Iberian Peninsula.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, most of the NE Spain AFLP fragments represent a subset of the total allelic variation found across the species, and all the analysed AFLP population diversity estimates ( hs , Hs , P 95 P 99 ) showed significant higher values in the southern Iberian populations of F. loscosii than in the northeastern Iberian ones (Table 1). These results concur with an allozyme study that also shows a higher allelic variability in the southern Iberian populations and an allelic sub‐representation in the NE Spain range (Pérez‐Collazos & Catalán 2008). The two independent molecular sources point towards to an earlier origin of the southern Iberian populations and a later derived origin of the northeastern ones; they also reject the AC hypothesis for this steppe plant in the Iberian Peninsula.…”
Section: Discussionsupporting
confidence: 91%
“…The intense agricultural pressure experienced in most parts of the southern and central Iberian ranges since Neolithic times might have contributed to a decrease in the number of the F. loscosii populations (cf. Pérez‐Collazos & Catalán 2008). The high levels of interpopulation differentiation (θ β = 0.399; < 44.04%; Table 2.1) might also reflect a common pattern observed in other endemic plant species that show the cumulative effects of stochastic processes resulting from reduced size populations, disrupted demography and selection by habitat modification (Hamrick & Godt 1989; Chung & Chung 1999; Chung & Park 2000; He et al .…”
Section: Discussionmentioning
confidence: 99%
“…(Apiaceae), which identified northern (Ebro valley) populations of this species as the result of more recent colonization. As in our results, these studies identified lower genetic diversity levels and more homogeneous genetic structure in northern (Ebro valley) populations relative to populations from southern and central parts of the range (Pérez‐Collazos & Catalán, ; Pérez‐Collazos et al ., ).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, previous studies of species in the Apiaceae family have shown variation at allozyme loci. In Ferula loscosii , a narrowly endemic species, 12 out of 17 tested enzyme systems could be interpreted in terms of Mendelian loci, and as many as 60% of these loci turned out to be variable (Pérez‐Collazos and Catalán 2008). In another study of a narrow endemic, Seseli farrenyi , nine out of 21 tested enzyme systems were resolved and 12 out of 14 loci scored showed polymorphism (López‐Pujol et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Electrophoresis was carried out on horizontal, 6×150×225 mm, 11% starch (Reppin PSG 1000) gels. Eight enzyme systems that have shown variation within several other plant species (Cronberg 1995, López‐Pujol et al 2002, Malm and Prentice 2002, van Rossum and Prentice 2004, Pérez‐Collazos and Catalán 2008) were screened for variation. Aspartate aminotransferase (AAT, EC 2.6.1.1), phosphoglucoisomerase (PGI, EC 5.3.1.9), phosphoglucomutase (PGM, EC 5.4.2.2) and menadione reductase (MNR EC 1.6.99) were best resolved with a lithium‐borate/Tris citrate buffer system (pH 8.3, 400 V, 25 mA 20 min, 50 mA ca 4 h).…”
Section: Methodsmentioning
confidence: 99%